Aplikasi Metode Double Exponential Smoothing Holt Dengan Optimasi Golden Section Untuk Peramalan Nilai Ekspor Provinsi Kalimantan Timur - Andini, Putri Dwiayu Aulia; Wahyuningsih, Sri; Siringoringo, Meiliyani (Program Studi Statistika FMIPA Universitas Mulawarman, 2024)
Exponential smoothing is a method of time series analysis used to forecast the future. The choice of forecasting method takes into account data patterns, such as Double Exponential Smoothing (DES) Holt is used on data that has a trend pattern, and Triple Exponential Smoothing (TES) Holt-Winters is used on trend and seasonal data. The aim of this research is to obtain the best forecasting method by optimizing the golden section on the export value of East Kalimantan Province from 2015 to 2022 and to obtain the results of forecasting the export value of East Kalimantan Province for the next 3 months using the best method by optimizing the golden section. The research results show that the parameter value using golden section optimization is for and for with a MAPE value of . Successive forecasting results in January 2023 are January 2023 is 3.503,201 million USD, February 2023 is 3.577,731 million USD, and March 2023 is 3.612,201 million USD.